Comparison of Fundamental Frequency between Monolingual and Bilingual Children with a Cochlear Implant - Bayat, Arash; Nikakhlagh, Soheila; Naderifar, Ehsan; Majlesi, Parisa; Moradi, Negin; Karimi, Majid; Bagheripour, Hossein; Majlesi, Manzar; Saki, Nader (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Background and Objective: Cochlear implantation influences acoustical and perceptual characteristics of voice in CI children. However, there is limited knowledge of the type and amount of influence of multilingualism on these characteristics of voice in CI children. The present study aimed to comparatively investigate fundamental frequency (F0) between two groups of bilinguals and monolinguals in children who recently underwent CI. Methods: This was a cross-sectional comparative study conducted on Persian-Arabic bilingual children (n=25) and monolingual Persian children (n=25) matched in age and gender. All children had congenitally profound hearing loss and received a unilateral CI before the age of two years. The participants were asked to sustain the vowel /a/ and vowel /e/ on a single breath for 4 seconds, and the F0 value was measured using Praat software. For each participant, the F0 was measured three times and then averaged as mean F0. Results: Our findings indicated no significant differences in terms of mean F0 for the vowels of /a/ and /e/ in monolingual and bilingual groups (p>0.05). Conclusion: Bilingual Persian-Arab children with CI display vocal characteristics that are largely comparable with those of their monolingual Persian peers with CI.